Kent gij dat volk : the Anglo-Boer War and Afrikaner identity in postmodern perspective (Historia, 2021)
Professional historians have proved resistant to the claims of postmodernism, which they see as highly theoretical, rather theatrical and decidedly threatening. As a result, the debate has become polarised, with proponents of postmodernism dismissing traditional historians as "positivist troglodytes", while reconstructionist and constructionist historians speak in "historicidal" terms of deconstructionism.
Keywords: Anglo-Boer War; Afrikaner; identity; postmodern; deconstructionism